Identification of Sustainable Contractor Supply Chain Patterns in Tasikmalaya City - Agi R. Hendardi; Dicky Nurmayadi; Thoriq Mustaqim (Jurnal Teknik Sipil dan Perencanaan, 2024)
The current supply chain is not just an activity but has moved towards effectiveness and efficiency of performance called the sustainable supply chain. With the threat of inefficiency, construction service business actors are expected to be able to manage the supply chain of their respective businesses. Specifically for the construction industry in Tasikmalaya City to manage the construction supply chain, this study was conducted with the title Identification of Sustainable Construction Supply Chain Patterns in Projects in Tasikmalaya City. This study aims to identify the supply chain system patterns of construction service companies, especially contractors, and what development patterns can be carried out by construction service companies to increase the competitiveness of construction service businesses in Indonesia through literature reviews and case studies on contractor companies in Tasikmalaya. This research method uses descriptive microanalysis from the results of semi-structured interviews. Data collection will be collected by direct interviews with construction project owners or managers in their respective projects. Based on the results of descriptive analysis of the information obtained, a general model is compiled that describes how the supply chain system pattern is carried out. The preparation of the supply chain pattern resulting from the identification will refer to the pattern developed by Susilawati in previous research, where the supply chain pattern has a relationship from the owner to the lowest subcontractor. This study identified three supply chain patterns where the pattern has a maximum of 4 tiers, and the selection of the supply chain pattern is based on the type of project being worked on and the company's ability to manage the project. The critical points for building an integrated supply chain are knowing the value desired by the client, building long-term relationships with suppliers, integrating activities, collaborating to manage costs, developing continuous improvement, and mobilizing and developing human resources.